Analisis Tingkat Kepuasan Tenant dan Upaya Peningkatan Kualitas Layanan di Kawasan Ekonomi Khusus XYZ dengan Quality Function Deployment - Mubarok, Abdul Faqih; Cahya, Handy Nur; Nuryanto, Imam; Damar, Haunan (Jurnal EMT KITA, 2026)
This research is motivated by the mismatch between the quality of industrial area services and tenant expectations. The study aims to examine the level of tenant satisfaction and formulate service quality improvement priorities in the XYZ Special Economic Zone (SEZ) using the Service Quality (SERVQUAL) and Quality Function Deployment (QFD) approaches. The research sample consisted of 30 respondents from six active tenant companies using a quantitative survey method. The study was conducted through SERVQUAL gap measurements and needs mapping in the House of Quality (HOQ). The results showed that the level of satisfaction was in the fair to good category, but all attributes still had positive gaps. The largest gaps were found in fiber optic/internet services and area security (1.23), followed by cleanliness (1.23) and road infrastructure in the assurance dimension (1.20). The main technical priorities include improving facility reliability, evaluating infrastructure based on tenant needs, implementing predictive maintenance, and strengthening service SOPs. These findings provide an operational basis for SEZ managers in determining service improvement priorities in a measurable manner based on tenant needs.